In vitro germination of Syagrus romanzoffiana (Cham.) Glassman - Rubio Neto, Aurelio; Machado, Caroline Araujo; Chagas, Edvan Alves; Costa , Barbara Nogueira Souza; Chagas , Pollyana Cardosos; Vendrame, Wagner Aparecido (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2020)
Syagrus romanzoffiana (Cham.) Glassman belongs to the Arecaceae family and is native to South America, with large importance as an ornamental plant. Therefore, the objective of this study was to evaluate TIS bioreactors for in vitro germination of queen palm. Traditional (agar-based) in vitro and TIS bioreactor technologies were compared. We evaluated parameters for the optimization of the tetrazolium test for seed viability and a protocol to increase germinated seedling survival after in vitro propagation. Fruits of S. romanzoffiana were collected in October 2017 from 5 individual trees located at the Tropical Research and Education Center, University of Florida. A total of 40 embryos were established in each culture system. The culture medium was refreshed every 30 days. Four replicates of 7 embryos were subjected to the tetrazolium test under different concentrations. Embryos were transferred to either a temporary immersion system in SETIS bioreactors using liquid medium or to test-tubes containing an agarbased semi-solid medium. After 45 days under in vitro conditions, germinated embryos were carefully removed from both the agar and liquid media, thoroughly washed and transferred to ex vitro conditions using small plastic pots. We have concluded that the TTC test can be successfully used to determine seed viability in S. romanzoffiana regardless of the TTC concentration evaluated in our study (0.25 to 1%). The traditional semi-solid in vitro system showed to be more effective for in vitro queen palm zygotic embryo germination compared to the TIS system. Seedlings from both systems showed similar growth characteristics. Index terms: Queen palm; bioreactors; embryo.